1970
DOI: 10.1177/00220345700490010201
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Electron Probe Microanalysis of Three Teeth Sections with Early Enamel Caries

Abstract: A detailed electron microprobe analysis of Ca, P, Na, Cl, and Mg in three early carious lesions is compared with data of these elements found in noncarious enamel of the same three specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1974
1974
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The formation of a more stable fluoridated mineral at the enamel surface would effectively increase the surface caries resistance, since this ion stabilizes the apatite crystal structure (37) and interferes physicochemically with caries development by reducing demineralization and enhancing remineralization (47). On the other hand, carbonate concentrations rise from the enamel surface towards the dentin (48,49). This may explain the increased demineralization of the inner enamel layers, because the carbonate fits less well in the lattice, generating a less stable and more acid-soluble apatite phase (37,50).…”
Section: Discussionmentioning
confidence: 99%
“…The formation of a more stable fluoridated mineral at the enamel surface would effectively increase the surface caries resistance, since this ion stabilizes the apatite crystal structure (37) and interferes physicochemically with caries development by reducing demineralization and enhancing remineralization (47). On the other hand, carbonate concentrations rise from the enamel surface towards the dentin (48,49). This may explain the increased demineralization of the inner enamel layers, because the carbonate fits less well in the lattice, generating a less stable and more acid-soluble apatite phase (37,50).…”
Section: Discussionmentioning
confidence: 99%
“…Other workers have examined thin ground sections of enamel by microradiography and electron probe analysis. [7][8][9] All such investigations have broadly confirmed many of the conclusions obtained previously by analysis of pooled enamel, which was ground in layers from the tooth surface toward the interior.10-12 For instance, density and calcium, phosphate, and fluoride con-This work was supported, in part, by Grants 180 centrations were shown to decrease, whereas magnesium, carbonate, and chloride concentrations were found to increase from the surface to the interior of the enamel. More detailed information obtained by these procedures, however, showed that the gradients of increase or decrease in concentration varied from place to place in the tooth.…”
mentioning
confidence: 99%
“…For the analysis of enamel, surface electron probe microanalysis (2) and secondary ion mass spectrometry (8) can be adopted only in vitro, the acid dissolution technique (4) in vivo as well. The acid dissolution is, however, destructive to the surface and it is difficult to measure e.g.…”
mentioning
confidence: 99%